Benign afebrile cluster convulsions with gastroenteritis: an observational study - Narchi Hassib (BMC, 2004)
Abstract Backround The occurrence of afebrile seizures in association with viral gastroenteritis, without dehydration or electrolyte imbalance, is virtually unknown outside Asia. They are reported to have a benign prognosis and not to require specific investigations or therapy. Methods We report the occurrence of such afebrile convulsions in association with viral gastroenteritis without dehydration or electrolyte imbalance, over a 3-year period, in a cohort of 14 British children. Results The children (5 males and 9 females, 10 Caucasians and 4 Asians) were aged 9 to 60 months (median 14.5 months). All 14 had a normal neurological examination and normal serum biochemistry. Twelve children had generalised seizures and 2 had, in addition, absence seizures. The number of seizures per child ranged from 1 to 8. Most convulsions were short with 85.7% of children having the longest seizure not longer than 4 minutes. The longest duration for a seizure was 10 minutes and occurred in 2 children. Convulsions did not recur after the first day in 10 children, 3 children had recurrences the second day and one child on the fourth day. No convulsions recurred after 4 days. Cerebrospinal fluid studies, computed tomography and electroencephalogram (EEG) were performed on two children who had prolonged seizures and the results were normal. No pathogenic bacteria were grown in any of the stools. Enzyme immunoassay detection of Rotavirus in the stools was positive in 7 of the 10 children where it was tested. All 14 children recovered spontaneously within a few days. On long-term follow of up to 31 months (median 16 months), none had further convulsions and all had normal development milestones. Conclusions Afebrile seizures in association with viral gastroenteritis do also occur outside Asia. Recognition of this entity should lead to reassurance of the parents. As in previously published series, investigations such as lumbar puncture, neuroimaging and EEG are usually normal and may not be necessary in most cases. Likewise, published data indicate that long-term anticonvulsant therapy is not usually warranted and the prognosis seems to be reassuring.